2018
DOI: 10.1111/bju.14412
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial impact of undergoing prostate cancer screening for men with BRCA1 or BRCA2 mutations

Abstract: This is the first study to report the psychosocial profile of men with BRCA1/BRCA2 mutations undergoing PCa screening. No clinically concerning levels of general or cancer-specific distress or poor quality of life were detected in the cohort as a whole. A small subset of participants reported higher levels of distress, suggesting the need for healthcare professionals offering PCa screening to identify these risk factors and offer additional information and support to men seeking PCa screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 45 publications
3
4
1
Order By: Relevance
“…When compared with normative data for the HADS score from a study of a large sample of general practice registrants in North West England,38 the prevalence of clinically significant anxiety and depression in carriers was not high. The HADS mean scores in carriers are also similar to those of other genetically high-risk populations 39 40…”
Section: Discussionsupporting
confidence: 67%
“…When compared with normative data for the HADS score from a study of a large sample of general practice registrants in North West England,38 the prevalence of clinically significant anxiety and depression in carriers was not high. The HADS mean scores in carriers are also similar to those of other genetically high-risk populations 39 40…”
Section: Discussionsupporting
confidence: 67%
“…Previous studies have reported a short-term increase in psychological distress in women undergoing breast cancer screening [ 40 , 47 , 58 ]. However, in the current study, similar to other high-risk populations (e.g., individuals who carry a BRCA1 , BRCA2 or TP53 pathogenic variant, or with a family history of breast and pancreatic cancer) undertaking MRI-based cancer surveillance, stable or decreased measures of psychological distress were reported [ 39 , 48 , 59 , 60 ]. In this study, some women with NF1 did demonstrate higher levels of anxiety and cancer worry prior to breast cancer screening, compared to other MRI-based screening studies [ 39 , 40 , 48 , 59 , 60 ], which persisted over the course of the study.…”
Section: Discussionsupporting
confidence: 50%
“…However, in the current study, similar to other high-risk populations (e.g., individuals who carry a BRCA1 , BRCA2 or TP53 pathogenic variant, or with a family history of breast and pancreatic cancer) undertaking MRI-based cancer surveillance, stable or decreased measures of psychological distress were reported [ 39 , 48 , 59 , 60 ]. In this study, some women with NF1 did demonstrate higher levels of anxiety and cancer worry prior to breast cancer screening, compared to other MRI-based screening studies [ 39 , 40 , 48 , 59 , 60 ], which persisted over the course of the study. Although the anxiety measures used in this study have not been commonly used in population studies in NF1, the higher rate of anxiety in NF1 is consistent with previous literature [ 18 , 21 ].…”
Section: Discussionsupporting
confidence: 50%
“…Results from previous studies in cancer patients showed that fear of cancer recurrence (FCR), defined as fear, worry, or concern about cancer returning or progressing, has been identified as one of the most common psychological challenges 8,9 . Studies on cancer worry in screening populations are limited and primarily conducted in screening populations with increased cancer risk 10,11 . Previous meta‐analyses in breast cancer screening have shown that false‐positive screening examinations affect psychosocial functioning that can persist for up to 3 years after the screening 12,13 .…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Studies on cancer worry in screening populations are limited and primarily conducted in screening populations with increased cancer risk. 10,11 Previous meta-analyses in breast cancer screening have shown that false-positive screening examinations affect psychosocial functioning that can persist for up to 3 years after the screening. 12,13 Available studies on screen-related psychological distress in CRC screening show that an adverse effect on psychological wellbeing exists.…”
Section: Introductionmentioning
confidence: 99%